Blowback : a warning to save democracy from the next Trump - Taylor, Miles (Security expert) (Atria Books, 2023)
"Donald Trump will be president again, whether he is on the ballot or not. That is because Trumpism is overtaking the Republican Party and will mount a vigorous comeback, potentially in the hands of a savvier successor--The Next Trump. This prophecy will come true, according to Miles Taylor, if we do not learn the lessons of the recent past. With the 2024 election approaching, the formerly "Anonymous" official is back with bombshell revelations and a sobering national forecast. Through interviews with dozens of ex-Trump aides and government leaders, Taylor predicts what could happen inside "Trump 2.0," the White House of a more competent and more formidable copycat. What sounds like a political thriller -- from shadowy presidential powers and CIA betrayals to angry henchmen and assassination plots -- is instead America's political reality, as Taylor uses never-before-told stories to shed light on the ex-president's unfulfilled plans, the dark forces haunting our civic lives, and to show how we can thwart the rise of extremism in the United States. Blowback is also a surprisingly emotional and self-critical portrait of a dissenter, one whose own unmasking provides a vivid warning about what happens when we hide the truth from others and, most important, from ourselves."-- Page 4 of cover.